2020
DOI: 10.3390/ijms21134774
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible Large-Scale Isolation of Exosomes from Adipose Tissue-Derived Mesenchymal Stem/Stromal Cells and Their Application in Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a fatal medical episode caused by sudden kidney damage or failure, leading to the death of patients within a few hours or days. Previous studies demonstrated that exosomes derived from various mesenchymal stem/stromal cells (MSC-exosomes) have positive effects on renal injuries in multiple experimental animal models of kidney diseases including AKI. However, the mass production of exosomes is a challenge not only in preclinical studies with large animals but also for succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 59 publications
3
63
3
Order By: Relevance
“…Previous studies described the role of AT-MSC exo in immune dysregulation, oxidative stress, and in ammation [41,42]. Lee et al showed that AT-MSCs had the ability to stably produce exosomes, and PRDX 1, 2, 4, and 6 exerted antioxidant activity to protect the kidney during acute injury [42]. Our data further con rm that exosomes play a role in immunity primarily by the regulation of leukocyte-mediated immunity.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies described the role of AT-MSC exo in immune dysregulation, oxidative stress, and in ammation [41,42]. Lee et al showed that AT-MSCs had the ability to stably produce exosomes, and PRDX 1, 2, 4, and 6 exerted antioxidant activity to protect the kidney during acute injury [42]. Our data further con rm that exosomes play a role in immunity primarily by the regulation of leukocyte-mediated immunity.…”
Section: Discussionsupporting
confidence: 80%
“…Considering their easy availability and fewer ethical issues, AT-MSCs may present a good choice for mass production of exosomes. Previous studies described the role of AT-MSC exo in immune dysregulation, oxidative stress, and in ammation [41,42]. Lee et al showed that AT-MSCs had the ability to stably produce exosomes, and PRDX 1, 2, 4, and 6 exerted antioxidant activity to protect the kidney during acute injury [42].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates the importance of MSC-Exo in disease treatment. Recently, it has been demonstrated that adipose and bone marrow MSC-derived exosomes have positive effects on wound healing pricess [40], acute kidney injury [41] , osteoarthritis [42], angiogenesis [43], liver brosis [44] and so on. hUCMSCs can secrete exosomes during various biological processes and hUCMSC-Exo also have emerged as potential therapeutic agents [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Among various separation methods, tangential ow ltration (TFF) is considered as an ideal method for industrial-scale production of sEVs [51][52][53]. TFF can provide GMP level sEVs from a large amount of CM [54]. Some studies have even shown that sEVs separated by TFF have higher yield and activity than those separated by ultracentrifugation [42,55].…”
Section: Discussionmentioning
confidence: 99%